Industrial property as a stimulator of scientific creation and innovation - Ion E. Anghel; Victor Iancu (Romanian Academy, National Institute for Economic Research, 2010)
In modern times, when progress is made through knowledge and knowledge is predominantly produced/used, industrial property rights, their protection and related specialized institutions play a stimulating role. Therefore, this paper presents first the requirements for stimulating scientific and technological creation and innovation in the European Research Area, in close relation to industrial property rights. In this context, we assess the size of scientific research and innovation in Romania in relation to industrial property rights. Considering the requirements for stimulating scientific and technological creation and innovation, we deal with issues on adapting and maintaining dynamism in law and institutional regulations, in order to achieve convergence, in general, and convergence in the industrial property field, in particular.
Keywords: O34; K29; P48; 330; adaptation; convergence; research&development; innovation; statistical indicators; industrial property; stimulation